Combating Information Disorder in Healthcare: A Vaccine Supply Chain Case - Dubois, Derek; Ashraf, Muhammad Hasan; Yalcin, Mehmet G.; Hos, Rabia (Journal of Business Logistics, 2026)
The COVID-19 vaccine supply chain faced unprecedented disruption from information disorder (collectively, misinformation, disinformation, and malinformation (MDM)). While prior research has examined the societal and health consequences of information disorder, little is known about how it disrupts supply chain management (SCM) or how supply chain actors respond. Guided by organizational information processing theory (OIPT) and stakeholder theory (ST), this study employs an embedded qualitative case study of the U.S. COVID-19 vaccine supply chain. We find that crisis-induced MDM functioned as an exogenous shock that heightened uncertainty and equivocality, overwhelming information-processing capacity, and fragmenting stakeholder responsibility. Downstream actors (i.e., pharmacies and clinicians) were disproportionately burdened in their efforts to combat MDM, relying largely on reactive tactics. Additionally, SC actors prioritized correcting false claims while deferring attribution of intent. This led to the conflation of misinformation and disinformation and the underdiagnosis of malinformation. By integrating OIPT and ST, we develop a framework that explains how information-processing misfit and shifting stakeholder salience jointly produce operational disruption and uneven accountability. Our findings extend SCM theory by conceptualizing MDM as a systemic supply chain risk and offer actionable guidance to improve resilience and trust. © 2026 The Author(s). Journal of Business Logistics published by Wiley Periodicals LLC.
Keywords: COVID-19; dept.grad; information disorder (MDM); organizational information processing theory; stakeholder theory; supply chain management

Unlocking the Linguistic Wealth - Dilsel Zenginliğin Keşfi: A Call for Bilingual Education in the Republic of Türkiye - DiCarlo, Lisa; Hoş, Rabia (Bilingual Review / La Revista Bilingüe, 2025)
As Türkiye transitions from a sending to a receiving country for migrants, it faces new challenges and opportunities. The country has experienced a significant influx of migrants, notably Syrian refugees, which has strained its educational infrastructure while also presenting potential benefits. The current article examines the role of Türkiye’s linguistic landscape in integrating diverse migrant populations, considering its historical emphasis on a singular national identity. Türkiye’s evolving sociocultural context invites a reassessment of linguistic diversity policies, particularly for national minorities and immigrant communities. We propose a systematic bilingual education program to foster a bilingual future in Türkiye, advocating for educational policies that preserve minority languages and encourage linguistic pluralism in an increasingly interconnected global society. Türkiye göçmen gönderen bir ülkeden göçmen alan bir ülkeye dönüşürken yeni zorluklar ve fırsatlarla karşı karşıyadır. Ülke, özellikle Suriyeli mülteciler olmak üzere önemli bir göçmen akını yaşadı ve bu durum eğitim altyapısını zorlarken aynı zamanda potansiyel faydalar da sundu. Bu makale, Türkiye’nin dilsel manzarasının çeşitli göçmen nüfuslarını entegre etmedeki rolünü, tekil bir ulusal kimliğe olan tarihsel vurgusunu göz önünde bulundurarak incelemektedir. Türkiye’nin gelişen sosyokültürel bağlamı, özellikle ulusal azınlıklar ve göçmen topluluklar için dilsel çeşitlilik politikalarının yeniden değerlendirilmesini gerektirir. Bu makalede Türkiye’de çift dilli bir geleceği teşvik etmek için azınlık dillerini koruyan sistematik bir çift dilli eğitim programı öneriyoruz ve artan bir şekilde dilsel çoğulculuğu teşvik eden eğitim politikalarını savunuyoruz.
Keywords: dept.grad

Empowering Newcomer Students with Inconsistent/Interrupted Formal Education (SIFE) in Secondary Schools: Urgent Call for Comprehensive Literacy Support - Hos, Rabia; Sari, Gulhan (The Literacy and Urban Schools Journal, 2025)
Keywords: dept.grad; peer-reviewed

Racial Literacy Development of Pre-Service Teachers: Exploring Race, Culture, Language, and Privilege through TESOL Course Work - Hos, Rabia; Seloni, Lisya (Preparing Antiracist ESOL Professionals: Linguistic Equity for Multilingual Learners, 2025)
This chapter presents a multi-institutional study that explores 38 pre-service English to Speakers of Other Languages (ESOL) teachers’ identity development in
Num Pages: 28
Keywords: dept.grad

Combating misinformation in the COVID-19 vaccine supply chain - DuBois, D.; Hoş, Rabia; Ashraf, Muhammad; Yalcin, Mehmet (Academy of Management Proceedings, 2025)
Keywords: Conceptual framework; Conceptual model; Misinformation; Stakeholder; Stakeholder engagement; Supply chain; Supply chain management; dept.grad

Bridging Borders: Teacher Perspectives on Refugee Students’ Schooling in Germany and the U.S. - Beck, Abby; Becker, Carmen; Hoş, Rabia (Multicultural Perspectives, 2025)
Keywords: Bridging (networking); Citizenship; Immigration; Qualitative research; Refugee; Teacher education; dept.grad

Syria, English in - Hadid, Alia; Hos, Rabia (The Wiley Blackwell Encyclopedia of World Englishes, 2025)
To gain a full perspective about English in Syria, it is necessary to focus on English learning in the past and present. The focus of the learning and teaching of the English language in Syria prior to 2011 consisted of various factors such as length of exposure to language, teacher preparation, qualifications, cross-linguistic transfer, and textbooks. The interruptions in schooling, brain drain, and depletion of resources were additional factors that influenced the learning and teaching of English in Syria in the post-2011 era. The entry concludes with a proposal that conscientious efforts are needed to enhance the teaching of English in Syria.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781119518297.eowe00398
Keywords: Computer science; English language teaching; English learning; Geography; History; Linguistics; Middle East; Philosophy; Syria; Syrian refugees; dept.grad; language education; teacher training

Empathy in action: nurturing sustainable educational change through Nel Noddings' ethics of care - Hadid, Alia; Hos, Rabia; Hauber-Özer, Melissa (Journal of Ethnic and Cultural Studies, 2025)
This introduction synthesizes the research presented by the contributors to this special issue to explore sustainable educational practices for refugees. A common thread across the articles is that they share components of Nel Noddings’ ethics of care framework, which emphasizes establishing welcoming, nurturing, and supportive environments that enable refugees to build meaningful relationships while honoring their cultural identities. We recommend action steps gleaned from the 11 papers in this issue that call for the concerted efforts of all those involved. Central to this vision are teachers, who serve as the backbone of the education system; however, to fulfill this role, they must be equipped with the necessary resources and skills to foster culturally responsive educational environments that emphasize students’ identities and provide equitable learning. This introduction underscores the importance of holistic and relational approaches as foundational to achieving sustainable educational equity for refugee learners.
Number: 2
Keywords: Community; dept.grad; empathy; empowerment; equity; inclusive; peer-reviewed

Reconceptualizing supply chain flows (SCFLOWS) - Ashraf, Muhammad Hasan; Yalcin, Mehmet G.; Hos, Rabia (The International Journal of Logistics Management, 2024)
Despite being a fundamental concept, the field of supply chain management (SCM) exhibits a significant lack of consensus regarding the definition of supply chain flows (SCFLOWS). Additionally, there has been an over-reliance on three flows – material, information and finance – while various other flows crucial to SCM performance have been overlooked. Hence, the purpose of this study is twofold: (1) to explore the multi-dimensional nature of SCFLOWS and (2) to identify additional flows beyond the commonly acknowledged ones that are vital for SCM performance.,This study employs various qualitative methods as part of the abduction process. The methods include in-depth interviews with logistics professionals, a Delphi study involving SCM scholars and a focus group comprising airline industry practitioners.,Seven SCFLOWS dimensions are identified and presented as SCFLOWS framework. Also, two additional flows, i.e. human and capital equipment, are proposed as vital to SCM performance.,This is the first study to introduce SCFLOWS framework to achieve consensus in the field. By introducing two additional flows, it proposes extending the SCFLOWS boundary to include various flows overlooked previously but pertinent to SCM performance. The SCFLOWS framework serves as a systematic guide to validate additional flows and represents an important step towards building SCM theory.
Keywords: dept.grad; peer-reviewed

Investigating the (Mis)alignment between Expenditures and Policy to Improve Multilingual Learner Programs - Correia, Amy; Hos, Rabia; Cahan, James (Journal of Educational Leadership and Policy Studies, 2024)
States and districts share an obligation to provide Multilingual Learners (MLLs) with access to high quality language programs that are proven to be effective in minimizing opportunity gaps between MLLs and non-MLLs. This article reviews how local education agencies (LEAs) allocated their state-issued funding to improve MLL language programs and increase student outcomes. Findings reveal that of the total state-issued MLL funding, LEAs used 88.7% on teacher salaries and benefits, 5.1% on teacher professional development, 4.9% on language program implementation, 0% on language program evaluation, and a small percentage of funding remained unspecified. Collectively, these findings indicate that LEAs did not adhere to the state's funding policies, nor did the state follow their own policies to regulate the LEAs' expenditures. We close with a discussion on how the state can improve their function as an organizational leader and serve as a model for other stakeholders in the shared obligation of the education of MLLs.
ERIC Number: EJ1431115
Keywords: Elementary Secondary Education; English (Second Language); English Language Learners; Expenditures; Financial Support; Fringe Benefits; Multilingualism; Outcomes of Education; Policy Analysis; Program Implementation; Program Improvement; Resource Allocation; School Districts; Second Language Learning; Second Language Programs; State Policy; Teacher Salaries; dept.grad

The effect of political risk on shareholder value and the mitigating role of corporate social responsibility (CSR) - Chatjuthamard, Pattanaporn; Jiraporn, Pornsit; Sarajoti, Pattarake; Singh, Manohar (Managerial Finance, 2020)
Purpose: The study investigates the effect of political risk on shareholder value, using an event study and a novel measure of firm-level political risk recently developed by Hassan et al. (2017). In addition, the authors explore how corporate social responsibility (CSR) influences the effect of political risk on shareholder wealth. Design/methodology/approach: The authors exploit the guilty plea of Jack Abramoff, a well-known lobbyist, on January 3, 2006, as an exogenous shock that made lobbying less effective and less useful in the future, depriving firms of an important tool to reduce political exposure. Findings: The results show that the market reactions are significantly more negative for firms with more political exposure. Additional analysis corroborates the results, including propensity score matching, instrumental-variable analysis and Oster's (2019) method for testing coefficient stability. Finally, the authors note that the adverse effect of political risk on shareholder value is substantially mitigated for firms with strong social responsibility, consistent with the risk mitigation hypothesis. Originality/value: This study is the first to explore the effect of political risk on shareholder value using a novel measure. Furthermore, it is also the first to show that CSR alleviates the cost of political risk to shareholders. © 2020, Emerald Publishing Limited.
2 citations (Crossref) [2023-10-31] tex.ids: chatjuthamardEffectPoliticalRisk2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086095623 type: Article
Keywords: CSR; Corporate social responsibility; Event study; Firm risk; G34; M14; Political risk; Shareholder wealth; dept.fin; dept.grad; peer-reviewed

CEO characteristics, firm performance, and corporate political contributions - Subrahmanyam, Vijaya; Singh, Manohar; Pennathur, Anita K. (Review of Financial Economics, 2020)
We investigate if CEO characteristics determine the choice of Political Action Committee (PAC) contributions by firms and if such participation leads to better firm performance. Using a unique, hand-collected database, we also focus on the identity of the politicians receiving PAC contributions to examine the impact of the value-relevance of such contributions. Examining data on corporate contributions made to candidates seeking federal office during the 2002, 2004, and 2006 election cycles, we find that CEO dominance and interest alignment influence strategic choices of firms with regards to establishing PACs. Our analysis of value-relevant contributions shows that firms prefer to donate to politicians representing the state of a firm's headquarters, validating the truth to the adage that all politics is local. However, these targeted political contributions do not have a discernible impact on firm performance.
2 citations (Crossref) [2023-10-31] tex.ids: lens.org/032-725-424-162-142, pop00254 tex.type: [object Object]
Keywords: CEO characteristics; CEO dominance; agency theory; corporate political contributions; dept.fin; dept.grad; firm performance; peer-reviewed